(3GdMjOI hGdGYJPGQ aj QO ef bGd HNdb GdbQBfs - (3CHh GdMSf YHO GdYRjR Hf eSde Gdecj GdcfGfj,J (B235 (3g` s
(3ChdgG (B:s
(3bGd bGd YHO GdYRjR Hf eSde GdcfGfi ZPG GJUd Hi hGfG HecI eG bO GXgQ HTQHf ZjGK GdeQjSi HHZOGO ef Gdbhd HNdb GdbQGf s
(3BNQgG (B:s
(3hcSQJ bhdge hMVJ MLJge hGHWdJ ePgHge HfU GdJfRjd HdG JChjd hdGJaSjQ hGdMeO ddg QH GdYGdejf Je cJGH GdMjOI HYhf Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B694s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds